Diarylamine‐Fused Subporphyrins: Proof of Twisted Intramolecular Charge Transfer (TICT) Mechanism. Issue 33 (15th May 2018) - Kise, Koki; Hong, Yongseok; Fukui, Norihito; Shimizu, Daiki; Kim, Dongho; Osuka, Atsuhiro
Abstract: Diarylamine‐fused subporphyrins 1 a and1 b were synthesized from β, β‐diiodo‐ meso ‐chloro subporphyrin 2 through a one‐pot procedure involving nucleophilic aromatic substitution and SRN 1‐type intramolecular fusion reaction as the first example of meso ‐nitrogen‐embedded subporphyrin. While non‐fused counterparts 3 b and4 b display effective fluorescence quenching due to twisted intramolecular charge transfer (TICT) in CH2 Cl2 at room temperature, 1 b emits fluorescence with Φ F =0.18 under the same conditions, because conformational twisting is not allowed due to the fused structure. In addition, the oxidative titration with tris(4‐bromophenyl)ammoniumyl hexachloroantimonate gave cation radical 7 for1 a and cation radical and dication for1 b . Actually, cation radical 7 was isolated through separation over silica gel column but was found to slowly decompose in concentrated solutions. Abstract : With a twist : meso ‐Diarylamine‐fused subporphyrins1 a and1 b were synthesized as the first examples of meso ‐nitrogen‐embedded subporphyrin. In contrast to non‐fused counterpart3 b, 1 b emits fluorescence ( Φ F =0.18) in CH2 Cl2 at room temperature, supporting the twisted intramolecular charge transfer (TICT) mechanism found in3 b . In addition, cation radial 7 was isolated from the oxidation of1 a with Magic Blue as a certainly stable species.